Investigation on mussel periostracum, a viscoelastic-to-poro-gel graded material, as an interface between soft tissue and rigid materials - Hyungbin Kim; Heejin Lim; Sangsik Kim; Jun Mo Koo; Chanoong Lim; Hojung Kwak; Dongyeop X. Oh; Dong Soo Hwang (NPG Asia Materials)
Abstract Mussel periostracum, a nonliving multifunctional gel that covers the rigid inorganic shells of mussels, provides protection against mechanical impacts, biofouling, and corrosion in harsh ocean environments. The inner part of the periostracum, which emerges from biological tissues, functions as a natural interface between tissue and inorganic materials. The periostracum shows significant potential for application in implantable devices that provide interfaces; however, this system remains unexplored. In this study, we revealed that the inner periostracum performs graded mechanical functions and efficiently dissipates energy to accommodate differences in stiffness and stress types on both sides. On the tissue end, the lightly pigmented periostracum exhibits extensibility and energy dissipation under repetitive tension. This process was facilitated by the slipping and reassembly of β-strands in the discovered major proteins, which we named periostracin proteins. On the shell end, the highly pigmented, mineralized, and porous segment of the periostracum provided stiffness and cushioned against compressive stresses exerted by the shell valves during closure. These findings offer a novel possibilities for the design of interfaces that bridge human tissue and devices.